Complete mitochondrial genome of the ragworm annelid Hediste diversicolor (of Müller, 1776) (Annelida: Nereididae). Issue 10 (3rd October 2021) - Gomes-dos-Santos, André; Hagemann, Andreas; Valente, Luísa; Malzahn, Arne M.; Monroig, Óscar; Froufe, Elsa; Castro, L. Filipe C.
Abstract: Marine annelids are a globally distributed and species-rich group, performing important ecological roles in macrobenthic communities. Yet, the availability of molecular resources to study these organisms is scarcer, comparatively with other phyla. Here, we present the first complete mitogenome of the Atlantic ragworm Hediste diversicolor (OF Muller, 1776). The mitogenome (15, 904 bp long) contains 13 protein-coding genes, 22 transfer RNA, and two ribosomal RNA genes, all encoded in the same strand. Gene arrangement and composition are identical to those observed in two available congeneric species, Hediste diadroma and Hediste japonica . The phylogenetic analysis using both maximum-likelihood and Bayesian inference methods reveal a well-supported monophyly of genus Hediste and the already reported paraphyletic relationships within the subfamilies Nereidinae and Gymnonereidinae. Our results highlight the relevance of increasing the molecular sampling within this diverse group of marine fauna.